PS01.201: A CASE OF GASTRO-STERNAL FISTULA OF GASTRIC TUBE AFTER ESOPHAGECTOMY: A CASE REPORT. (14th September 2018) - Kato, Daiki; Yamada, Kazuhiko; Soma, Daisuke; Nohara, Kyoko; Yamashita, Satoshi; Kataoka, Atsuko; Wake, Hitomi; Yokoi, Chizu; Kokudo, Norihiro
Abstract: Background: Peptic ulcer occurring in the gastric tube after esophagectomy sometimes penetrates into the mediastinal structures. We reported a case of sternal penetration of gastric tube ulcer successfully treated. Methods: A CASE REPORT: Results: A 73-years-old man who had undergone video-assisted thracoscopic esophagectomy (VATS) with 3-field lymphadenectomy reconstructed by retrosternal route after neoadjuvant chemo-radiation therapy. He visited outpatient complaining mild pain and redness of skin on anterior chest wall after 7 months of esophagectomy. Computed tomography (CT) revealed gastric tube ulcer penetrated into sternum. Upper GI endoscopy showed active ulcer in lower gastric tube. Biopsy was confirmed no malignant cell but bone tissues. He was admitted and started medication of proton pomp inhibiter and nutritional therapy. After 1 month he was improved symptoms and endoscopic findings. Conclusion: There was a rare case of penetration into sternum due to gastric tube ulcer. In the literatures, 4 cases were reported about penetration into sternum. All four cases had symptoms of pain and redness of skin and were diagnosed with upper GI endoscopy and CT. Two cases underwent surgery and another cases were treated conservational therapy. Disclosure: All authors have declared no conflicts of interest.